Changes in the Thermal and Hydrometeorological Forest Growth Climate During 1948–2017 in Northern Germany - Bat-Enerel, Banzragch; Weigel, Robert; Leuschner, Christoph (Frontiers in Forests and Global Change, 2022)
Recent severe droughts and climate change projections have caused rising worries about the impacts of a warmer and drier climate on forests and the future of timber production. While recent trends in thermal and hydrometeorological climate factors have been studied in many regions on earth, less is known about long-term change in climate variables most relevant for tree health and productivity, i.e. temperature (T), precipitation (P), climatic water balance (CWB), and SPEI aridity index in early and mid-summer, when leaf unfolding and peak stem growth take place. Here, we analyze T, P, CWB, and SPEI trends separately for all growing season months (April-September) during the 1948-1982 (before the recent warming) and 1983-2017 periods (after the onset of warming) in their spatial variation across the North German Lowlands based on a dense climate station network. While trends in thermal and hydrometeorological variables were weak from 1948 to 1982, we find a significant decrease in April precipitation and increase in July precipitation from 1983 to 2017 throughout much of the study region, while June precipitation has decreased locally by 10 mm or more (or up to 20 %). The cumulated growing-season CWB has deteriorated by up to 30 mm from 1948-1982 to 1983-2017 in most of the region except at the North Sea coast, where it became more favorable. Recent climate aridification is more pronounced in the drier South-east of the study region with a more continental climate, as indicated by stronger negative P, CWB, and SPEI trends for April, May, and June. We conclude that water availability especially in the physiologically important months April and June has deteriorated in the larger part of the North German Lowlands since the 1980s, increasingly impairing hydrometeorological forest growth conditions. The identified trends may serve as early warning signals of anticipated future loss in tree vitality.